Late onset recurrence of clinical signs after surgery for intervertebral disc extrusion in French bulldogs. (26th March 2021) - Kerr, S.; Crawford, A. H.; De Decker, S.
Abstract : Objectives: To identify the prevalence of recurrence of clinical signs after initial successful decompressive surgery for intervertebral disc extrusion in French bulldogs. Materials and Methods: A medical record search was performed to identify French bulldogs that experienced an initial successful outcome after surgery for thoracolumbar or cervical intervertebral disc extrusion. Collected information included signalment, neurological examination findings, intervertebral disc extrusion location, presence of vertebral malformations, kyphosis, type and extent of surgery. Decompressive surgery was not followed by extensive prophylactic fenestrations. Follow‐up information was retrieved from medical records and telephone interviews with referring veterinary surgeons. Results: Eighty‐four French bulldogs with thoracolumbar (n=55) or cervical (n=29) intervertebral disc extrusion were included. Forty‐three (51%) dogs that had decompressive surgery for thoracolumbar (n=29) or cervical (n=14) intervertebral disc extrusion suffered recurrence of signs. The median time between decompressive surgery and recurrence of clinical signs was 9 months and 21 days. Of the 29 dogs suffering recurrence of clinical signs following surgery for thoracolumbar intervertebral disc extrusion, 24 returned for recurrence of clinical signs localised to the thoracolumbar segments, while five returned for recurrence of signs localised to the cervical region. Of the 14 dogs who suffered recurrence of signs following surgery for cervical intervertebral disc extrusion, nine returned for signs localised to the cervical region, while five returned for clinical signs localised to the thoracolumbar region. Clinical Significance: This study suggests a high rate of late onset recurrence of clinical signs after decompressive surgery for intervertebral disc extrusion in French bulldogs. This information can aid in the management of owner expectations.